148 ECG abnormalities in COVID-19 pneumonia: acute pericarditis, silent cad, or both? A case report. (8th December 2021) - Franco, Erica; Visconti, Massimiliano; Taglialatela, Vittorio; Panella, Silvana; Rovera, Chiara; Conti, Valentina; Iancu, Dana Miruna; Raineri, Michele; Corgnati, Giuditta; Marangoni, Ludovica; Picardi, Elisa; Solaro, Cristina; et al.
Abstract: Aims We report the case of a hypertensive 70 year-old man, who presented to the Emergency Department (ED) with fever, dry cough, malaise, dyspnoea. A nasopharyngeal swab for SARS-CoV-2 test was done, being positive. Methods and results Chest TC demonstrated ground glass bilateral pneumonia. Laboratory test showed WBC 10680/mmc, CRP 20 mg/l, TnT 0.03 ng/l, NTproBNP 147 ng/l. The liver and kidney function were within normal values. ECG was normal. He was treated with high flow oxygen (cPAP), enoxaparin, dexamethasone, doxycycline. After an initial improvement, dyspnoea got worse in 8th day, with the evidence of a new rise of inflammatory markers (PCR 95 mg/l, IL6 49 pg/ml) and the clinical new onset of cardiac rubbings on medical examination. The ECG revealed a sinus rhythm with T wave inversion everywhere. TnT remained normal. Echocardiography revealed a normal ventricular function, without segmentary alterations, absence of valvular disease. A mild pericardial effusion was evidenced, without signs of tamponade. We treated the patient with tocilizumab, after exclusion of other active infective foci. The clinical response was good, the patient was progressively weaned by oxygen and he was discharged asymptomatic. After 15 days, for ECG alterations persistence, despite no signs of ACS, a Coronary TC was done and a subcritical multivessel coronary artery disease was demonstrated: a subcritical IVA stenosis and a calcific MO. Conclusions In conclusion we report a successful treatment of COVID pneumonia likely complicated by acute pericarditis, and we observe that in these patients hypoxemia and cytochine storm possibly bring out silent vascular diseases, otherwise neglected.